Accuracy of Estimating Periodontitis and Its Risk Association Using Partial-Mouth Recordings for Surveillance Studies: A Systematic Review and Meta-Analysis. (17th March 2022) - Alawaji, Yasmine N.; Alshammari, Abdulsalam; Aleksejuniene, Jolanta
Abstract : Objectives . Our aim is to conduct an up-to-date systematic review and meta-analysis pertaining to the accuracy of using the partial-mouth recording protocol (PRP) in surveillance studies to estimate the periodontitis prevalence, extent, severity, and its risk associations. Methods . Medline and Embase databases were searched for studies which assessed the periodontitis prevalence, severity, extent, or its risk associations using PRPs versus full-mouth recording protocols (FRPs); searches were conducted up until May 26, 2021. The risk of bias and the applicability of the studies were assessed using the QUADAS-2 tool. Both qualitative data synthesis and quantitative data synthesis were performed, and comparisons were done for the accuracy and precision of PRPs for different periodontitis outcomes. The study's protocol was registered through the International Platform of Registered Systematic Review and Meta-analysis Protocols (registration number: INPLASY202160032). Results . A total of 14 studies were included. The studies had a considerable degree of heterogeneity, along with a moderate risk of bias and applicability concerns. Several factors influenced the accuracy or precision of using PRPs, including the age, distribution of periodontitis in the studied population, PRP selection, total PRP sites, the threshold for minimum sites with CAL, and the severity of periodontitis case definitions. Overall, the PRP with the highest accuracy and precision mainly included (1) a full-mouth protocol at the following partial sites: mesiobuccal-midbuccal-distolingual (MB-B-DL), mesiobuccal-distolingual (MB-DL), mesiobuccal-midbuccal-distobuccal (MB-B-DB), mesiobuccal-distobuccal (MB-DB), and 84 sites using the random site selection method (RSSM) and (2) random-half-mouth (RHM) protocols. Conclusions . The PRPs with the highest overall accuracy and precision in estimating the periodontitis prevalence, extent, severity, and risk associations included the full-mouth assessment at the following partial sites: MB-B-DL, MB-DL, MB-B-DB, MB-DB, and 84 sites using RSSM and RHM protocols.